Optical Emission Spectroscopy for Studying Fe Plasma Parameters Produced by Exploding Wire Technique in Carbon Nanotubes - Water Colloid - Fathi, Sabah M.; Kadhim, Saba J. (Iraqi Journal of Science, 2022)
The goal of this work is to study plasma parameters for Fe plasma generated by exploding wire (EEW) in carbon nanotubes-water colloid with three current values (50, 100 and 150)A. In this research, the plasma electron temperature (Te), the electron density (ne), electron density (ne), plasma frequency(f p), Debye length (λD) and Debye number (ND) were found for Fe produced by Arc discharge plasma. Boltzmann plot was used to calculate the plasma electron temperature (Te);electron density (ne) was calculated from Stark broadening. It was found that the electron temperature values increased from (0.4134 _ 0.415) eV and the electron density increased from( 0.93 - 1.16)× 1017cm-3.